Documenting and Assessing Learning in Informal and Media-Rich Environments - Lemke, Jay (The John D. and Catherine T. MacArthur Foundation Reports on Digital Media and Learning, 2015)
An extensive review of the literature on learning assessment in informal settings, expert discussion of key issues, and a new model for good assessment practice. Today educational activities take place not only in school but also in after-school programs, community centers, museums, and online communities and forums. The success and expansion of these out-of-school initiatives depends on our ability to document and assess what works and what doesn't in informal learning, but learning outcomes in these settings are often unpredictable. Goals are open-ended; participation is voluntary; and relationships, means, and ends are complex. This report charts the state of the art for learning assessment in informal settings, offering an extensive review of the literature, expert discussion on key topics, a suggested model for comprehensive assessment, and recommendations for good assessment practices. Drawing on analysis of the literature and expert opinion, the proposed model, the Outcomes-by-Levels Model for Documentation and Assessment, identifies at least ten types of valued outcomes, to be assessed in terms of learning at the project, group, and individual levels. The cases described in the literature under review, which range from promoting girls' identification with STEM practices to providing online resources for learning programming and networking, illustrate the usefulness of the assessment model.